2021
DOI: 10.1136/bmjno-2020-000084
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on stroke admissions in Qatar

Abstract: IntroductionThe COVID-19 pandemic has resulted in a dramatic unexplained decline in hospital admissions due to acute coronary syndromes and stroke. Several theories have emerged aiming to explain this decline, mostly revolving around the fear of contracting the disease and thus avoiding hospital visits.AimsIn this study, we aim to examine the impact of the COVID-19 pandemic on stroke admissions to a tertiary care centre in Qatar.MethodsThe Hamad General Hospital stroke database was interrogated for stroke admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…Data sources and study selection [5][6][7][8][9][10][11][12][13][14][15], and severe [NIHSS >15] strokes) before and during the pandemic. Wherever the mean±SD of NIHSS or onset-to-door time were not reported, they were estimated from the median and interquartile range.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data sources and study selection [5][6][7][8][9][10][11][12][13][14][15], and severe [NIHSS >15] strokes) before and during the pandemic. Wherever the mean±SD of NIHSS or onset-to-door time were not reported, they were estimated from the median and interquartile range.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6] A decrease in stroke admissions during the first peak of the pandemic was reported from Asia, Europe, North and South America. [7][8][9][10][11][12][13][14] While the decrease was predominantly recorded for those with milder symptoms, presentation for all stroke subtypes decreased substantially. This was suggested by decrease in the utilization of the computed tomography perfusion based rapid processing of perfusion and diffusion (RAPID, iSchemaView, Redwood City, CA, USA) software for acute stroke imaging in a report from USA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the MENA region, like other parts of the world, a decrease in hospital admissions of stroke patients has been observed. This was also accompanied by a decrease in mechanical thrombectomy and intravenous thrombolysis procedures [ [24] , [25] , [26] ].…”
Section: Objectives and Methodsmentioning
confidence: 99%
“…[ 25 ]. In a retrospective study from Qatar, an increase in stroke due to large vessel occlusion (LVO) was found, despite the overall reduction in stroke admission as a result of decline in stroke mimics [ 26 ]. The increase in LVO can be explained in part by an increased prothrombotic state as has been described in severe COVID-19 infections.…”
Section: Objectives and Methodsmentioning
confidence: 99%